Enfermar, envejecer y morir en los tiempos de Tito a Trajano - Segura Ramos, Bartolomé (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
Illness and its typology; ageing and the manner of understanding old age, and, finally, the death as well as how to treat it, and the frame of mind before these three plagues of humanity from the part of the writers which describe such events, are the target this paper aims at. The work is limited both from the temporal point of view (between Titus and Trajanus, namely, forty years circa), as well as from the point of view of the authors considered, vz., Plinius, Martial, Statius, Iuvenal. Analysis and possible diagnostics of the illnesses; curiosity for knowing how antiquity faced up to old age and its opinion about it; reaction of the writers before the death, are others aspects that constitute a principal part of the achieved work.